Lussazione dell’articolazione sternoclavicolare - D’Arrigo, C.; Rota, P.; De Sanctis, S. (Lo Scalpello - Journal, 2019)
DISLOCATION OF STERNOCLAVICULAR ARTICULATION Dislocation of the sternoclavicular joint is a rarely injury. Dislocations can be anterior or posterior. Anterior dislocation is a usually relatively benign injury, while posterior dislocations may be very serious. In addition to the standard projections, there are also special views for joint evaluation. Computed tomography remains the gold standard. In anterior dislocations, and degree I and II posterior instability, the treatment is conservative, while in case of degree III dislocations, the treatment consists in closed reduction. Operative stabilisation must be considered if closed reduction is unsuccessful.